Atherosclerosis After Kidney Transplantation: Changes of Intima-Media Thickness of Carotids During Early Posttransplant Period - Nafar, Mohsen; Khatami, Farideh; Kardavani, Babak; Farjad, Reza; Pour-Reza-Gholi, Fatemeh; Firoozan, Ahmad (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate atherosclerotic changes in the carotid artery following kidney transplantation. Materials and Methods: Twenty-six nonsmoker kidney allograft recipients who did not have cardiovascular disease or diabetes mellitus were enrolled in the study. The carotid intima-media thickness (IMT) was measured at 12 points using B-mode ultrasonography. The mean of the measured values was considered as the patientâ€™s IMT. We followed the patients and changes in the carotid IMT were evaluated every 2 months up to the 6th posttransplant month. Results: Â The mean age of the patients at transplantation was 41.5 Â± 11.1 years.Â The mean baseline IMT was 0.84 Â± 0.22 mm. During the follow-up period it reached 0.85 Â± 0.22 mm, 0.87 Â± 0.23 mm (P = .01), and 0.88 Â± 0.24 mm (P = .002) after 2, 4, and 6 months, respectively. The IMT measures significantly correlated with the age and body mass index. Using the IMT cutoff points of 0.75 mm for stroke and 0.82 mm for MI, we found that 57.7% and 68% of the patients were at the risk of stroke at baseline and 6 months after transplantation (P < .001).Â Also, 46.2 % of the patients were at the risk of MI at baseline that rose to 53.8% at the end of the study (P < .001). Conclusion:Â Atherosclerosis is an early event after kidney transplantation even in asymptomatic patients and those without major risk factors such as cardiovascular disease, diabetes mellitus, and smoking. Early diagnosis and treatment of atherosclerosis is of utmost importance